2009
DOI: 10.1007/s10278-009-9226-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Accuracy Factors in the Determination of Postoperative Acetabular Cup Orientation Using Hybrid 2D–3D Registration

Abstract: Single standard anteroposterior radiograph-based methods for measuring cup orientation following total hip arthroplasty (THA) are subject to substantial errors if the individual pelvic orientation with respect to X-ray plate is not taken into consideration. Previously, we proposed to use a hybrid 2D-3D registration scheme to determine the postoperative acetabular cup orientation and developed an object-oriented cross-program called "HipMatch." However, its accuracy and robustness have not been fully investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The results of the experiments that were conducted on datasets of ten cadavers (20 hips) demonstrated that the present technique was apparently more accurate than the radiographic measurement method. The substantial error range (from 0.2 • to 15.2 • ) as found in measuring anteversion using the radiographic measurement method [11] in this study is coincident with other recently published findings that the radiographic measurement of anteversion is unreliable [8][9][10][13][14][15]24,25]. The advantages of the present technique over other methods for post-operative calculation of acetabular cup orientation are apparent.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results of the experiments that were conducted on datasets of ten cadavers (20 hips) demonstrated that the present technique was apparently more accurate than the radiographic measurement method. The substantial error range (from 0.2 • to 15.2 • ) as found in measuring anteversion using the radiographic measurement method [11] in this study is coincident with other recently published findings that the radiographic measurement of anteversion is unreliable [8][9][10][13][14][15]24,25]. The advantages of the present technique over other methods for post-operative calculation of acetabular cup orientation are apparent.…”
Section: Discussionsupporting
confidence: 87%
“…The advantages of the present technique over other methods for post-operative calculation of acetabular cup orientation are apparent. Several studies [8][9][10][13][14][15]24,25], including the one presented in this paper, have shown that the radiographic measurement methods, though easy to use, cannot produce accurate results due to the wide variability in individual pelvic orientation relative to X-ray plate during image acquisition. Post-operative CT-based method, which is regarded as the most reliable method for measuring post-operative cup orientation [8][9][10][13][14][15]34,35], cannot be used in clinical routine due to the additional expense and radiation doses to the patient associated with its acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because projecting the 3D pelvic geometry onto a 2D plane may not reflect the accurate position of the pelvis, particularly the complex posterior rings, researchers have tried to develop more advanced methods for determining the 3D position using 2D imaging tools. Previous image registration and processing methods have used pre‐operative 3D CT reconstruction and intra‐operative radiography, particularly in spinal and arthroplastic surgery‐related research . Hufner et al performed image registration based on the regular shape of the external fixture, which could improve the accuracy of the registration and spatial orientation.…”
Section: Discussionmentioning
confidence: 99%